Culturally Responsive Teaching as a Strategy to Improve Students' Science Literacy in Higher Education - Fahrur Rozi; Yusnadi; Retno Dwi Suyanti; Yusron Abda'u Ansya (Jurnal Penelitian Pendidikan IPA, 2025)
The problem in this research is the low level of science literacy among students caused by learning that is less responsive to cultural contexts. The objective of this research is to examine the application of culturally responsive teaching in improving science literacy among university students in higher education. The method used is a systematic literature review of 40 scientific articles published between 2019 and 2025, obtained from the Scopus and Google Scholar databases. Data analysis was conducted through the stages of planning, implementation, and reporting, referring to PRISMA guidelines, and identifying patterns, themes, and key findings from each article. The research results show that a culturally responsive learning approach, such as the integration of local cultural values, the use of socio-cultural contexts in learning, and the creation of inclusive relationships between lecturers and students, can enhance students' science literacy. Improvements occurred in critical thinking skills, contextual understanding of science concepts, and learning motivation. The conclusion of this study is that culturally responsive teaching significantly contributes to the enhancement of science literacy and has the potential to be an inclusive and transformative pedagogical strategy in higher education settings.